Incretin Effect in Women with Former Gestational Diabetes within a Short Period after Delivery. (19th April 2012) - Pacini, G.; Tura, A.; Winhofer, Y.; Kautzky-Willer, A.
Abstract : Background and Aims . Women with former gestational diabetes (fGDM) are characterized by impaired beta-cell function (BC). Incretin hormones contribute to insulin secretion after oral administration of glucose. We aimed to assess the possible role of incretins on altered insulin release in fGDM. Materials and Methods . We studied 104 fGDM women within 6 months after delivery and 35 healthy women after normal pregnancy (CNT) with a 75 g oral (OGTT) and a 0.33 g/kg intravenous (IVGTT) glucose test, both lasting 3 h. The ratio of suprabasal areas under the concentration curves for glucose (dAUC GL ) and C-peptide (dAUC CP ) evaluated BC during OGTT (BC OG ) and IVGTT (BC IV ). Incretin effect was computed in all fGDM and in fGDM with normal tolerance (fGDM NGT ) and with impaired glucose regulation (fGDM IGR ). Results . dAUC GL of fGDM was higher (P < 0.0001 ) than CNT for both tests; while dAUC CP were not different. BC OG and BC IV were lower in fGDM versus CNT (1.42 ± 0.17 nmol CP /mmol GLUC versus 2.53 ± 0.61, P = 0.015 and 0.41 ± 0.03 versus 0.68 ± 0.10, P = 0.0006, respectively). IE in CNT (66 ± 4 %) was not different from that of all fGDM (59 ± 3 ) and fGDM NGT (60 ± 3 ), but higher than that of fGDM IGR (52 ± 6 ; P = 0.03 ). IE normalized to BMI was 2.77 ± 0.19 % m 2 /kg in CNT, higher than that of fGDM IGR (1.75 ± 0.21 ; P = 0.02 ) and also of fGDM NGT (2.33 ± 0.11 ; P = 0.038 ). Conclusion . Compromised IE characterizes fGDM IGR . In both fGDM categories, regardless their glucose tolerance, IE normalized to BMI was reduced, signifying an intrinsic characteristic of fGDM. Therefore, the diminished IE of fGDM seems to reflect an early abnormality of the general beta-cell dysfunction in the progression toward type 2 diabetes.